Response of growing Rabbits to different plant fibre sources - Dairo, F. A. S.; Agunbiade, S. O.; Durojaiye, B.; Onisile, D. S.; Adegun, M. K.; Oluwasola, T. A. (Nigerian Journal of Animal Science, 2023)
Four different browse plant leaf meals namely, Gliricidia sepium, Leucanea leucocephala, Tridax procumbens and Aspilia Africana were included separately as dietary fibre source in rabbit diets during which growth performance, nutrient digestibility and haematology were monitored. Thirty 7 weeks old weaner rabbits with initial weight range 753±13.46g -766.58± 4.87 were divided into 5 groups and fed each of the diets that constituted the treatments for 56 days with wheat offal as dietary fibre source in the control. Significantly higher (p<0.05) and similar average daily feed intake (ADFI) was recorded by rabbits fed the control and Gliricidia sepium diets (57.02 ± 0.92g; 56.62± 0.96g respectively) while those on Aspilia Africana (47.61± 0.99 g) and Tridax procumbens (48.7± 0.36g) were similar and lowest (p<0.05). The final live weight (FLW), average daily body weight gain (ADWG), feed conversion ratio (FCR) and protein efficiency ratio (PER) were significantly better (p<0.05) in rabbits fed diets containing Aspilia africana (1.91±0.03 kg; 20.38 ± 0.52 g and 2.34 ± 0.10; 2.59 ± 0.11 respectively) even though similar to values from Tridax procumbens and the control diets. The nutrient digestibility viz; dry matter (DM) Crude protein (CP), neutral detergent fibre (NDF) and acid detergent fibre (ADF) were similar and higher (p<0.05) in rabbits fed Aspilia Africana (81.44 ±0.75%, 68.26 ± 0.35, 56.14 ± 0.13, 53.61 ± 0.08% respectively) and the control diets. The pack cell volume (PCV), haemoglobin concentration (Hbc), red blood cell count (RBC), white blood cell count (WBC) and blood glucose level were not affected (p>0.05) by the dietary fibre sources. Aspilia africana and Tridax procumbens appeared to be a good plant fibre dietary source in growing rabbit than Gliricidia sepium and Leucanae leucocephala.